2011
DOI: 10.1210/jc.2010-1439
|View full text |Cite
|
Sign up to set email alerts
|

Association of 25(OH)D and PTH with Metabolic Syndrome and Its Traditional and Nontraditional Components

Abstract: Serum 25(OH)D, but not PTH, was significantly associated with MetS as well as a number of MetS components after multivariate adjustment. These results suggest that low 25(OH)D may play a role in the etiology of the MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
77
1
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 35 publications
8
77
1
8
Order By: Relevance
“…(2) What is the 'optimal' oral supplemental dose of vitamin D (taking into account all sources, including UVB exposure and dietary intake) in severely obese individuals, both before and after bariatric surgery? In conclusion, in this review the relationship between low circulating 25-hydroxyvitamin D and obesity was discussed, including potential mechanisms through which each might impact the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) What is the 'optimal' oral supplemental dose of vitamin D (taking into account all sources, including UVB exposure and dietary intake) in severely obese individuals, both before and after bariatric surgery? In conclusion, in this review the relationship between low circulating 25-hydroxyvitamin D and obesity was discussed, including potential mechanisms through which each might impact the other.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Obesity and these related issues contribute significantly to modern healthcare costs, morbidity and mortality. 4,5 Furthermore, weight loss is difficult to achieve and sustain, and consequently many individuals, especially those who already have significant co-morbidities, are turning to bariatric weight loss surgery as a way to effectively treat obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a growing body of evidence has demonstrated extraskeletal associations of both vitamin D (25-OH-D) (1-3) and parathyroid hormone (PTH) (4)(5)(6), with particular focus on their metabolic implications. Several studies have suggested that low levels of vitamin D may play a role in the development of type 2 diabetes mellitus (T2DM) (7)(8)(9).…”
mentioning
confidence: 99%
“…Furthermore, deterioration in b-cell function has been suggested as a pathophysiologic mechanism through which lower vitamin D may increase the risk of T2DM (10,11). Previous studies have also reported that increased PTH is associated with insulin resistance (12) and metabolic syndrome (4,13), and deterioration of insulin sensitivity and b-cell function has been described in hyperparathyroid states (14). Conversely, however, many investigators have questioned the association of vitamin D and PTH with glucose metabolism, particularly in light of several observational studies (13,(15)(16)(17)(18) and interventional trials (1,(19)(20)(21) that either have been negative or showed only modest beneficial effects of vitamin D supplementation on glucose homeostasis.…”
mentioning
confidence: 99%
“…The prevalence of MS is remarkably high in CKD patients, being approximately 30% -65% for non-dialysis patients (6-8) and 47% -69% for dialysis patients (9-12). MS represents a global epidemic and it is clearly important to explore new, non-traditional risk factors.In the general population, MS has been positively associated with serum intact parathyroid hormone (iPTH) (13-15) and negatively with vitamin D status, as measured using 25-hydroxyvitamin D (25(oH)D) concentrations (16)(17)(18)(19)(20). Decreased vitamin D levels and elevated iPTH levels may play critical roles in the etiology of MS, either through an association with the Correspondence to: Jie Dong,…”
mentioning
confidence: 99%